2022
DOI: 10.14202/vetworld.2022.2705-2714
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the potential of Kazakhstani pork in the global market of meat products: Problems and prospects

Abstract: Background and Aim: Pig farming is integral in developing Kazakhstan's animal husbandry as it has shown rapid growth in profit and a high turnover. Industrial pig products have significant global demand, particularly in China and Russia. However, as pig farming is a small-scale industry with insufficient mechanization and automation in Kazakhstan, the costs have increased while the quality of Kazakhstani pig products has decreased due to the simultaneous influx of cheap imported pork into the domestic market. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The concept of sustainable development drives the development of a model of an enterprise with an active environmental stance. This concept is believed to be one of the most pervasive in the global community and is supported by countries at different levels of development (Dambaulova et al, 2022). The development of this concept originated from the environmental activities of the United Nations, and in Russia, it was first enshrined in presidential decrees in 1994 and 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of sustainable development drives the development of a model of an enterprise with an active environmental stance. This concept is believed to be one of the most pervasive in the global community and is supported by countries at different levels of development (Dambaulova et al, 2022). The development of this concept originated from the environmental activities of the United Nations, and in Russia, it was first enshrined in presidential decrees in 1994 and 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Dambaulova et al . [ 8 ] reported that one of the main factors contributing to the natural loss of pigs is the irrational organization of animal feeding, which may include inadequate nutrition, poor feed quality, improper feeding schedules, or inconsistent feeding practices. Notably, one of the fundamental principles of animal welfare is “good feeding,” which refers to providing animals with appropriate and high-quality nutrition to promote comfort and overall well-being [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the economic development of pig farming, the availability of high-quality feed that is efficiently utilized plays a crucial role because feed costs typically account for a considerable portion of the cost structure of livestock products, reaching approximately 65%-70% [7]. Dambaulova et al [8] reported that one of the main factors contributing to the natural loss of pigs is the irrational organization Available at www.veterinaryworld.org/Vol.16/November-2023/4.pdf of animal feeding, which may include inadequate nutrition, poor feed quality, improper feeding schedules, or inconsistent feeding practices. Notably, one of the fundamental principles of animal welfare is "good feeding," which refers to providing animals with appropriate and high-quality nutrition to promote comfort and overall well-being [9].…”
Section: Introductionmentioning
confidence: 99%